Bimbingan Belajar Gratis sebagai Upaya Social-Distancing bagi Siswa di SMP Negeri 2 Lintong Nihuta - Lastri Wahyuni Manurung; Supriandi Sihotang; Eva Vronika Hasugian; Yolanda Adelina Lumban Gaol; Griffit Spanyer Indrawaty Nababan (Indonesia Berdaya, 2022)
Many efforts have been made by the government to create order in social distancing. By providing free tutoring online, outside of school hours, it can be an alternative to avoid the possibility of meeting between students after school hours. In addition to reducing crowds, tutoring can also improve student learning outcomes so that students of SMP Negeri 2 Lintong Nihuta don't spend time after school to meet or gather with other people, but by studying online as was done in the free tutoring for this service. . This activity can support the government's program in reducing the spread of the COVID-19 virus, namely maintaining social distancing. The partners in this community service are students of SMP Negeri 2 Lintong Nihuta who have received approval from the principal. This activity is carried out for one month. Students are taught online so students can stay in their own homes